The effects of interleukin-21 in the biology of transplant rejection - Zeng, Xiandong; Pan, Yixiao; Xia, Qiang; He, Kang (Frontiers in Immunology, 2025)
Interleukin-21 (IL-21) is a cytokine that plays a crucial role in regulating immune responses, affecting various immune cell types, including T cells, B cells, natural killer (NK) cells, and dendritic cells. IL-21 is primarily produced by CD4+ T cells, particularly follicular helper T (Tfh) cells and Th17 cells, and has been shown to be extensively involved in regulating both innate and adaptive immunity. IL-21 is particularly significant in the differentiation, proliferation, and effector functions of T cells and B cells. In the context of organ transplantation, IL-21 contributes to the promotion of acute transplant rejection and the development of chronic rejection, which is primarily antibody-mediated. This review summarizes relevant studies on IL-21 and discusses its multifaceted roles in transplant immune rejection, providing insights into therapeutic strategies for either inhibiting graft rejection or promoting tolerance. It also explores the feasibility of blocking the IL-21 signaling pathway within current immunosuppressive regimens, aiming to provide further clinical references.